Gene Expression Of Some Antibiotic Resistance Mechanisms In Neisseria Gonorrhoeae Isolated From Iraqi Patients - Kazaal, Meraim A.; oudah, Marwah Ali (South Eastern European Journal of Public Health, 2024)
Background: Treatment of N. gonorrhoeae infection is restricted by the rising commonness of multidrug-resistance strains. The point of this study was to evaluate antibiotic resistance and mRNA expression of penA, pilQ, norM, farA, and mtrE of N. gonorrhea. Method: one hindered samples collected from patients infected with N. gonorrhoeae. The bacteria were isolated and diagnosed using culture media and biochemical tests. Using the MIC method, the sensitivity of bacteria to penicillin, ciprofloxacin, ceftriaxone, spectinomycin, tetracycline, and azithromycin was determined. After RNA extraction and cDNA production, gene expression of penA, pilQ, norM, farA, and mtrE was assessed using real time -qPCR. Results: we found all isolates sensitive to ceftriaxone and azithromycin. Clear increase in penA, pilQ, farA, and mtrE gene expression of penicillin-resistant isolates (1.571, 3.135, 0.010 and 34.24 respectively), while norM gene expression decreased in those isolates. High gene expression for pilQ, farA, and mtrE among isolates resistant to ciprofloxacin (0.0041, 0.00072, 0.011 respectively). Tetracycline-resistant isolates appeared to have higher gene expression for penA, norM, farA, and mtrE (0.0033, 8.669, 37.85, 15.84 respectively). Spectinomycin-resistant isolates have high gene expression for penA, pilQ, norM, farA, and mtrE (0.222, 0.021, 0.036, 0.0002, 19.63 respectively) . Moreover, gene expression of penA, norM, and farA increased in males (6.938, 1.095, 7.946 respectively) while the rate of gene expression for pilQ and mtrE increased in females (0.161 and 7.832 respectively). Conclusion: gene expression of penA, pilQ, norM, farA, and mtrE increased in most antibiotics resistance isolates especially of bacterial infection that isolated from males.